Menerapkan Berpikir Kritis Dalam Kehidupan Sehari-Hari : Studi Kasus Penanganan Berita Hoaks - Nur Halimah; Purwanti (Journal of Media and Communication | E-ISSN : 3063-9581, 2025)
The digital era brings easy access to information, but also presents challenges in the form of the spread of hoax news that misleads the public. This study discusses the importance of critical thinking as a key skill in facing these challenges. Critical thinking involves evaluating, analyzing, and understanding information objectively, so that individuals can distinguish fact from opinion, identify bias, and make informed decisions. Steps such as verifying information sources, looking for supporting evidence, and developing a healthy skeptical attitude are important strategies in filtering information and avoiding hoax traps. With critical thinking skills, individuals can not only protect themselves from false information, but also contribute to the creation of a healthier and more responsible information environment.